RELATIONSHIP BETWEEN THE PSYCHOLOGICAL CONTRACT AND JOB SATISFACTION OF FACULTY MEMBERS IN PRIVATE UNIVERSITIES - Majumdar, Amrita (JBFEM, 2020)
The modern academic world is undergoing a sea-change. There was a time when only government institutions were present to offer education to humankind. Now, a lot of private institutions, in addition to the Government institutions, are serving society. In this world, the role of teachers cannot be ignored. The psychological contract plays a remarkable role in meeting the faculty members’ unsaid expectations and management of private universities. The study was conducted with the faculty members of private universities considering the four states of eastern India (Bihar, Orissa, Jharkhand and West Bengal) to identify the factors affecting the psychological contract of faculty members and its impact on job satisfaction. Appropriate statistical tools were applied to measure the above. The findings of the research will help the management of the private Universities to decide on the organizational policy.